Endogenous and induced angiogenic characteristics of human chorion-derived stem cells - Fariha, MMN; Chua, KH; Tan, GC; Lim, YH; Nur Fariha Mohd Manzor (Wiley, 2024)
Cell-based therapy using stem cells has emerged as one of the pro-angiogenic methods to enhance blood vessel growth and sprouting in ischaemic conditions. This study investigated the endogenous and induced angiogenic characteristics of hCDSC (human chorion-derived stem cell) using QPCR (quantitative PCR) method, immunocytochemistry and fibrin-matrigel migration assay. The results showed that cultured hCDSC endogenously expressed angiogenic-endogenic-associated genes (VEGF, bFGF, PGF, HGF, Ang-1, PECAM-1, eNOS, Ve-cad, CD34, VEGFR-2 and vWF), with significant increase in mRNA levels of PGF, HGF, Ang-1, eNOS, VEGFR-2 and vWF following induction by bFGF (basic fibroblast growth factor) and VEGF (vascular endothelial growth factor). These enhanced angiogenic properties suggest that induced hCDSC provides a stronger angiogenic effect for the treatment of ischaemia. After angiogenic induction, hCDSC showed no reduction in the expression of the stemness genes, but had significantly higher levels of mRNA of Oct-4, Nanog (3), FZD9, ABCG-2 and BST-1. The induced cells were positive for PECAM-1 (platelet/endothelial cell adhesion molecule 1) and vWF (von Willebrand factor) with immunocytochemistry staining. hCDSC also showed endothelial migration behaviour when cultured in fibrin-matrigel construct and were capable of forming vessels in vivo after implanting into nude mice. These data suggest that hCDSC could be the cells of choice in the cell-based therapy for pro-angiogenic purpose.